Impact of soaking cows housed in a tunnel-ventilated, evaporative-cooled barn in Thailand - D.V. Armstrong; John F. Smith; V Wuthironarith; Joseph P. Harner (Kansas Agricultural Experiment Station Research Reports, 2004)
Ten multiparous lactating Holstein cows were arranged in a replicated 5 x 5 Latin Square design to evaluate the effect of soaking frequency and volume of water per soaking on lactating cows housed in a tunnel-ventilated and evaporative-cooled freestall barn. Rectal temperature, respiration rate, and body surface temperatures were measured every 5 minutes. Treatments were: control (C); soaking every 5 minutes with 0.26 gallons (5L); soaking every 5 minutes with 0.53 gallons (5H); soaking every 10 minutes with 0.26 gallons (10L); or soaking every 10 minutes with 0.53 gallons (10H). Average ambient temperature and humidity were 86.5ºF and 68% outside the barn, and 80.4ºF at 86% inside the barn, respectively. Water having a temperature of 80.6ºF was applied manually from the shoulder to the tail. Treatments were applied after three initial measurements were assessed. Seventeen measurements were made during treatment application and five measurements after the treatments were stopped. Air velocity over the shoulder of the cows was 4 mph. Respiration rate and body surface temperature for all treatments were less than those of the control, except for rear udder surface temperature in the 10L treatment. Rectal temperature for 5L, 5H, and 10H were less than those of the control. Respiration rate for 5L and 5H were less than that of 10L. These data indicate that soaking can be used in combination with tunnel ventilation and evaporative pads to reduce heat stress.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heat stress; Cooling Systems; Facilities